PREVALENCE OF ENDO-PERIO LESIONS AMONG ADULT PATIENTS. AN OBSERVATIONAL STUDY - Timea Dako; Ana-Petra Lazăr; Maria-Alexandra Mârṭu; Luminița Lazăr (Romanian Dental Association for Education, 2021)
Background: Endo-perio lesions (EPL) are challenging for any clinician, and altough relatively rare in clinical practice, they can severely compromise the longterm prognosis of the tooth. These combined lesions require multidisciplinary approach in both steps of diagnosis and therapy. Hence, the present study was undertaken to investigate the prevalence of endo-perio lesions, and several factors that can contribute to the onset and progression of the disease. Materials and methods: A total of 1548 periapical x-rays were analyzed in search of EPL. Complete demographic data was obtained from all patients. Descriptive statistic tests were applied to determine the prevalence of EPL and independent effects of gender, age and smoking history on the progression of the illness. Results: Out of 1548 patients, 4% presented with EPL. By analysing the age, gender and smoking history factors, most EPL were found in male patients, among the age group of 61-70 with a smoking history. Conclusion: The prevalence of EPL among adult patients was low and it was influenced by several demographic factors such as older age, male gender, and smoking history.